A study on the effect of arterial stiffness, ocular perfusion pressure and genetics on the severity and progression of glaucoma. - Tajuddin, Liza Sharmini Ahmad (Pusat Pengajian Kesihatan, 2015)
Inadequate blood supply to the optic nerve head (ONH) has been implicated for glaucomatous damage based on the vascular theory of glaucoma. Ocular perfusion pre^ure (OPP) is the balance of systemic blood pressure and intraocular pressure (IOP). OPP is believecf play an important role in maintaining the function of retinal nerve fiber layer (RNFL). Low OPP is believed to cause further damage to the RNFL. There was significant association of low OPP with severity of glaucoma in this study. However, there was no association with progression of glaucoma.Ocular perfusion may also be affected by the stiffness of the vessels and endothelial dysfunction. There was significant association of endothelial dysfunction with severity of glaucoma. Systemic arterial stiffness seem not to affect the severity of glaucoma. Susceptibility genetic markers for glaucoma in Malay patients were also identified. ABCC5 was found to significantly associated with PACG in Malay patients. There was several markers that reached genome wide association significant in Malay patients with POAG.